Acyldepsipeptide antibiotics kill mycobacteria by preventing the physiological functions of the ClpP1P2 protease. Issue 2 (1st April 2016) - Famulla, Kirsten; Sass, Peter; Malik, Imran; Akopian, Tatos; Kandror, Olga; Alber, Marina; Hinzen, Berthold; Ruebsamen‐Schaeff, Helga; Kalscheuer, Rainer; Goldberg, Alfred L.; Brötz‐Oesterhelt, Heike
Summary: The Clp protease complex in Mycobacterium tuberculosis is unusual in its composition, functional importance and activation mechanism. Whilst most bacterial species contain a single ClpP protein that is dispensable for normal growth, mycobacteria have two ClpPs, ClpP1 and ClpP2, which are essential for viability and together form the ClpP1P2 tetradecamer. Acyldepsipeptide antibiotics of the ADEP class inhibit the growth of Gram‐positive firmicutes by activating ClpP and causing unregulated protein degradation. Here we show that, in contrast, mycobacteria are killed by ADEP through inhibition of ClpP function. Although ADEPs can stimulate purified M. tuberculosis ClpP1P2 to degrade larger peptides and unstructured proteins, this effect is weaker than for ClpP from other bacteria and depends on the presence of an additional activating factor (e.g. the dipeptide benzyloxycarbonyl‐leucyl‐leucine in vitro ) to form the active ClpP1P2 tetradecamer. The cell division protein FtsZ, which is a particularly sensitive target for ADEP‐activated ClpP in firmicutes, is not degraded in mycobacteria. Depletion of the ClpP1P2 level in a conditional Mycobacterium bovis BCG mutant enhanced killing by ADEP unlike in other bacteria. In summary, ADEPs kill mycobacteria by preventing interaction of ClpP1P2 with the regulatory ATPases, ClpX or ClpC1, thus inhibiting essential ATP‐dependent protein degradation. Abstract : The mechanism of action of antibiotic acyldepsipeptides (ADEP) has been commonly accepted to function by activating unregulated protease activity of bacterial ClpP peptidase. Here, we show enhanced killing by ADEP upon depletion of the ClpP1P2 level in a conditional Mycobacterium bovis BCG mutant. Our data reveal killing of mycobacteria by ADEPs through abrogating the interaction between ClpP and its cognate Clp‐ATPases rather than ClpP activation like in many other bacteria.